Proposta de modelo de gestão consorciada de resíduos da construção civil (RCC) na Unidade de Gerenciamento do Rio São João-MG (MB 13) - Maia, Mariele Corrêa dos Reis (2019)
Population growth and uncontrolled progress contribute to the generation of construction waste (CDW), when inadequately disposed of, cause environmental liabilities and affect the quality of life of society. In order to establish guidelines for the management of these, CONAMA Resolution No. 307 was created in 2002, however, the municipalities, mainly small ones and stakeholders involved, had difficulties in implementing the system due to the lack of financial resources, technical staff and supervision. Timely measures to remedy such impacts are joint actions, where municipalities work together to achieve economic and environmental benefits. Thus, this research aimed to characterize the current management of CDW in the 10 small municipalities that make up the São João River management unit (MB-13): Bom Jesus da Penha, Fortaleza de Minas, Itaú de Minas, Jacuí, Pratápolis, São Pedro da União, Cássia, Nova Resende, Passos and São Sebastião do Paraiso, in order to propose a model of management consortium to provide decisions. The Soft System (SSM) methodology established seven stages: documentary, field research, bibliographic review, diagnosis, data compilation and analysis of the actors involved in structuring the intermunicipal consortium. It was verified that in 80% of the municipalities the responsibility of the management of the CDW is of the public power, of which it lacks resources directed to the activity, besides finding them arranged in disorderly ways and places, without distinction of classes and care of the dangerousness. They do not have infrastructures such as ecopoints, ATTs, class A landfills and recycling plants. In the other 20%, the management is directed to companies of bucket, who are responsible for the final destination of the waste and some areas properly licensed. The builders do not present PGCDW and the PMGCDW public administration, they claim difficulties in complying with the guidelines established by the resolution, do not have collectors and transporters records, legislation, supervision and educational actions. In the unit, class A waste is predominant, with a similar percentage incidence among builders, denoting standardization of the construction processes. In this scenario, the management consortium was structured as Steps for the administrative headquarters of the association and 4 groups for the exercise of activities: Clusters 1 and 2 are composed of 4 municipalities and a landfill each, together comprise a mobile recycling plant, which will act in the ecopoints of each municipality for a period of 7 days. Clusters 3 and 4 operate in isolation due to the volume of CDW and territorial area, with the first 4 ecopoints, one ATT, one class A and one recycling plant operating for 30 days, and the second, 5 ecopoints, 2 ATT, 2 class A landfills and a recycling plant operating for 30 days in each ATT. The system will share services, technical and administrative staff, with an estimated cost of implementation of R $ 2,645,766.75 financed by own resources, state, federal or agreements. Due to its sustainable character, the short-term operational cost is managed by the municipalities' contribution, proportional to the volume of CDW generated and the use of infrastructures and services, and later with financial resources produced by the system itself.